Elements of the artistic synthesis in making a powerpoint presentation - Naumenko, Nataliia (My University, 2024)
Learning the novelty requirements for PowerPoint presentation in creating an image of a food product, one of which is the expedient usage of artistic synthesis, is the prospective trend not just for technologists, but also for the students majoring in advertisement, marketing, edition and polygraph practice

Вивчення вимог новизни до презентації PowerPoint у створенні образу харчового продукту, однією з яких є доцільне використання художнього синтезу, є перспективним напрямком не лише для технологів, а й для студентів спеціальностей реклама, маркетинг, видавництво та поліграф. практика
Keywords: artistic synthesis; sensory images; image of a product; художній синтез; сенсорні образи; зображення продукту; кафедра іноземних мов професійного спрямування